2012
DOI: 10.3892/mco.2012.50
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous liver and bone metastasis from small early gastric carcinoma without lymph node involvement: A case report

Abstract: Abstract.A 65-year-old man was referred to our Hospital for examination of gastric cancer initially diagnosed by medical check-up. Esophagogastroduodenoscopy demonstrated a superficial depressed-type gastric cancer in the antrum, and abdominal computed tomography showed no evidence of distant metastases. A tumor measuring 11 mm in diameter was removed by endoscopic submucosal dissection (ESD). Since histological examinations of ESD specimens showed a well-differentiated adenocarcinoma invading the submucosal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
(34 reference statements)
0
14
0
Order By: Relevance
“…While overexpression of HER2 is a factor that is associated with poor prognosis in patients with breast cancer, its association with prognosis in patients with gastric cancer is widely debated (25). For this reason, improvements in the accuracy of HER2 testing and further research on this topic are required (26,27). Nonetheless, the survival advantage provided by trastuzumab plus chemotherapy in patients with HER2-positive gastric cancer has been confirmed, with data showing that this regimen is efficacious and safe.…”
Section: No Patients -----------------------------------------------mentioning
confidence: 97%
“…While overexpression of HER2 is a factor that is associated with poor prognosis in patients with breast cancer, its association with prognosis in patients with gastric cancer is widely debated (25). For this reason, improvements in the accuracy of HER2 testing and further research on this topic are required (26,27). Nonetheless, the survival advantage provided by trastuzumab plus chemotherapy in patients with HER2-positive gastric cancer has been confirmed, with data showing that this regimen is efficacious and safe.…”
Section: No Patients -----------------------------------------------mentioning
confidence: 97%
“…A number of studies have reported a favorable prognosis after curative resection of EGC by endoscopic resection [5][6][7][8]. Although the 5-year overall survival and 5-year disease-specific survival rates of patients with EGC after curative therapy are more than 97% and 99% respectively [7][8][9], there have been several reports of EGC recurrence after curative treatment, which can lead to unfavorable outcomes [8,10,11]. After curative endoscopic resection, the recurrence rate ranges from 4.5% to 16%.…”
Section: Introductionmentioning
confidence: 99%
“…In EGCs, the rate of solitary liver metastasis is about 0.4–0.7% . It is correlated with the presence of the angio‐lymphatic invasion and is higher than 5% in lymph node‐metastatic EGC .…”
Section: Metastatic Behavior Of Egcmentioning
confidence: 99%
“…Early gastric cancer is considered a carcinoma confined to either the gastric mucosa (pT1a) or submucosa (pT1b), which is independent of the presence of lymph node metastases or other clinicopathological characteristics . Tumors smaller than 5 mm in diameter are considered minute carcinomas, but 3–9% of them are pT1b stage and can be metastatic .…”
Section: Definition and Classic Parameters Of Egcmentioning
confidence: 99%
See 1 more Smart Citation